Arabic Language Learners as an Example of Their Willingness to Communicate in a Second Language (L2-WTC) Accomplishment - Maryani, Novy; Ardiansyah, Ade Arip; Hasan, Ahmad Mohammed (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Willingness to communicate in a second language (L2-WTC) is a crucial factor influencing the success of language learning, particularly in the context of Arabic learning. This article presented the extent to which Arabic language learners' willingness to communicate (WTC) in a second language impacts their achievement in acquiring language skills. A quantitative approach was used and the study surveyed 33 undergraduate Arabic learners at UIN Bandung in 2023. Data were collected through questionnaires measuring WTC levels and the factors influencing them, such as motivation, speaking anxiety, and opportunities for language practice. Statistical analysis was conducted to identify the relationship between WTC and the Arabic language proficiency learners. The results indicated that a high level of WTC is positively associated with better communicative competence. Additionally, learning motivation and environmental support significantly contribute to enhancing students' WTC. On the other hand, speaking anxiety and limited practice opportunities were identified as barriers to achieving optimal WTC. This article recommends that Arabic language instructors focus on teaching strategies that can enhance WTC, such as creating supportive environments and reducing speaking anxiety. Further research is suggested to explore the role of technology in supporting WTC and to investigate other individual factors such as cultural and social backgrounds.